2007
DOI: 10.1007/s11199-007-9344-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sport Commentator Framing on Viewer Attitudes

Abstract: An experimental analysis was conducted to determine the effects of involvement, commentator framing, and gender on viewer attitudes toward female athletes. The sample was comprised of 112 students at a midwestern university in the United States. Hypotheses and research questions were tested through a 2×3 multivariate analysis of covariance (MANCOVA). Results indicated the overall MANCOVA was significant. Involvement was positively related to viewer attitudes' towards the dependent variables and explained 27.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Bruening and Dixon (2007) report on the gendered nature of the workplace and how substantially it can impact female coaches who are also mothers. Parker and Fink (2007) provide evidence that males still possess less favorable attitudes towards female athletes, regardless of their level of involvement as fans of women's sports. Angelini (2007) reports that women are happier watching women participate in feminine sports, an indication that only certain sports are "acceptable" for the female athlete, even among female viewers.…”
Section: Introductionmentioning
confidence: 82%
“…Bruening and Dixon (2007) report on the gendered nature of the workplace and how substantially it can impact female coaches who are also mothers. Parker and Fink (2007) provide evidence that males still possess less favorable attitudes towards female athletes, regardless of their level of involvement as fans of women's sports. Angelini (2007) reports that women are happier watching women participate in feminine sports, an indication that only certain sports are "acceptable" for the female athlete, even among female viewers.…”
Section: Introductionmentioning
confidence: 82%
“…The articles in the Special Issue have adopted varied methodological approaches, including indepth semi-structured qualitative interviews (Bruening and Dixon 2008;Claringbould and Knoppers 2008;FieldingLloyd and Mean 2008;Hoeber 2008;Ross and Shinew 2008), critical discourse analyses (Knoppers and Anthonissen 2008), participant observations (Anderson 2008), survey research (Avery et al 2008), and laboratory experiments (Angelini 2008;Parker and Fink 2008). The diversity of approaches to the study of sex and gender in sport organizations provides an encompassing perspective-one that allows for a more complete understanding of gender in the workplace.…”
Section: Varied Methodologiesmentioning
confidence: 99%
“…Many of the studies in this area lack a critical analysis of how gender might influence men's and women's reactions to sport and their motivation for consuming it. As a departure from this trend, both Angelini (2008) and Parker and Fink (2008) provide strong theoretical rationale for their study of sport consumers. Angelini drew from multiple perspectives, including social identity theory and social cognitive theory, to examine women's emotional responses to gendered sport portrayals.…”
Section: Theoretical Focusmentioning
confidence: 99%
“…Parker and Fink (2008) found that U.S. college students (male and female), who reported being a fan and following women's basketball, had more positive attitudes towards female athletes and their athletic abilities as compared to less involved viewers. It is possible that boys and men who follow women's sports or particular female athletes are more likely to respect female athlete's athleticism and respond positively to media coverage of female athletes.…”
Section: Perceptions Of Performance Athletesmentioning
confidence: 96%